Discovery of Novel Biomarkers of Therapeutic Responses in Han Chinese Pemetrexed-Based Treated Advanced NSCLC Patients - Zhang, Xiaoqing; Zhang, Di; Huang, Lihua; Li, Guorong; Chen, Luan; Ma, Jingsong; Li, Mo; Wei, Muyun; Zhou, Wei; Zhou, Chenxi; Zhu, Jinhang; Wang, Zhanhui; et al. (Frontiers in Pharmacology, 2019)
Pemetrexed, one of the most commonly used drugs in advanced non-small cell lung cancer (NSCLC) therapies, often leads to various therapeutic responses in patients. These therapeutic responses to pemetrexed, including adverse drug reactions (ADRs) and its intended therapeutic effects, have been demonstrated to be highly individual-specific. Such difference in therapeutic responses across individual may be caused by the unique genetic variations in each patient. However, only a few pemetrexed-based studies have been performed using Han Chinese patients. In this study, we aimed to identify genetic signatures of therapeutic responses of pemetrexed-based treatment using 203 Han Chinese advanced NSCLC patients. All the participants received 2 different types of therapies: (1) treatment with only pemetrexed; (2) treatment with both pemetrexed plus platinum (mainly cisplatin and carboplatin). We then performed a genetic association analysis on 16 selected SNPs in 7 genes using these 2 groups. The analysis of patients receiving only pemetrexed suggested that the SNP rs1051298 on SLC19A1 gene (c.*746C>T) increased the risk of all ADRs (collected all types of ADRs) in different cycles of pemetrexed therapy (1-2 cycle: P = 0.0059, OR = 3.143; 1-4 cycle: P = 0.0072, OR = 2.340; 1-6 cycle: P = 0.0071, OR = 2.243). This influence of rs1051298 is particularly significant in terms of liver injury (1-4 cycle: P = 0.0056, OR = 3.863; 1-6 cycle: P = 0.0071, OR = 3.466). In all the patients, including patients who received both pemetrexed plus platinum, SNP rs1801133 on MTHFR gene (665C>T) was found to be significantly associated with hematological ADRs in 1-2 cycle (P = 0.0079, OR = 3.566). Additionally, we discovered that SNP rs12995526 (c.815-102T>C) in the ATIC gene and SNP rs11545077 (c.91G>T) in the GGH gene were associated with both ADRs and therapeutic effects. In sum, our study identified several potential biomarkers that were significantly associated with ADRs and therapeutic effects of pemetrexed-related treatments using Han Chinese patients. Our discoveries will provide important clues for personalized pemetrexed-based treatment design that is for Han Chinese NSCLC patients in the future.